Coumarin-Mediated Growth Regulations, Antioxidant Enzyme Activities, and Photosynthetic Efficiency of Sorghum bicolor Under Saline Conditions - Sultana, Robina; Wang, Xiukang; Azeem, Muhammad; Hussain, Tabassum; Mahmood, Athar; Fiaz, Sajid; Qasim, Muhammad (Frontiers in Plant Science, 2022)
Secondary metabolites, such as phenolic compounds, play an essential role in alleviating salt-induced negative effects in plants. The present study focused on priming and foliar applications of a potent phenolic compound (coumarin) to Sorghum bicolor var. SS77 seeds to induce salt tolerance in the seedlings. Based on a previous investigation on the germination and seedling growth of sorghum by seed priming with two different concentrations of coumarin (50 and 100 ppm lower and higher dosages, respectively), a higher dosage was found to be more effective and therefore selected for further investigation in the present study. A greenhouse experiment was conducted and applied the coumarin 100 ppm dosage as (i) a seed priming application (COP), (ii) a foliar application (COF) and (iii) both a seed priming and foliar application (COPF) under 100 and 200 mM NaCl concentrations. All coumarin treatments (COP, COF and COPF) showed a significant increase (P˂ 0.01) in plant growth, photosynthetic pigments, antioxidant enzyme activities and photosynthetic efficiency of PSII at all tested salinities compared to the controls (nonprimed). Salt stress highly reduced vegetative growth, antioxidant enzymatic activities, photosynthetic performance and biochemical attributes in nonprimed sorghum plants. However, the COPF treatment led to a maximum increase in growth, photosynthetic pigments, antioxidant enzymes and photosynthetic efficiency. This approach is low cost and improves salt tolerance in the important high biomass crop Sorghum bicolor to fulfill the food, fodder and energy demands of the ever-growing population.